Determinan Terhadap Kepatuhan Wajib Pajak Melalui Sanksi Sebagai Pemoderasi - Widia Puja Putri Dyani; Achmad Badjuri (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Motor vehicle tax is a regional tax collected by the government, the more taxes collected will improve infrastructure improvements for the welfare of the people in Indonesia. Taxpayer compliance greatly affects tax revenue. The purpose of this study was to show the effect of knowledge, service quality, and socialization on taxpayer compliance with sanctions as moderation. This research uses quantitative methods. The number of samples is 100 respondents with the slovin formula who are vehicle taxpayers registered at the Kendal Samsat. The sampling technique is accidental sampling. Primary data used by distributing questionnaires. The test results can be concluded that the variable knowledge, service quality has an effect on taxpayer compliance, but socialization has no effect on taxpayer compliance. This study also proves that sanctions are able to moderate the relationship between knowledge and service quality on taxpayer compliance, while sanctions do not moderate the relationship between socialization and taxpayer compliance. Keywords: Taxpayer Knowledge, Service Quality, Tax Dissemination, Tax Sanctions, and Taxpayer Compliance.